Causally inferred evidence of the impact of green and blue spaces (GBS) on maternal and neonatal health: a systematic review and meta-analysis - Rukun K S Khalaf; Selin Akaraci; Faye D Baldwin; Rebecca S Geary; Ruwanthi Kolamunnage-Dona; Ruth F Hunter; Sarah E Rodgers (Environmental Research: Health)
The benefits of green and blue space (GBS) exposure on improving public health are accepted by a range of stakeholders, including policy makers. Extensive GBS research into health supports the theory that GBS promotes physical activity and has mental restorative and environmental mitigative properties. Studies exploring the impact of GBS exposure on maternal, prenatal, and/or neonatal health have mainly utilised cross-sectional methods. This does not allow for causal inference. Thus, our systematic review aimed to analyse the evidence of the impact of GBS on maternal, prenatal, and/or neonatal health. Our study adhered to PRISMA guidelines. We searched seven online databases (Medline, Scopus, Web of Science, PsycInfo, Embase, Environment Complete, and Maternity & Infant Care Database) and excluded cross-sectional studies without mediation analysis. Our risk of bias assessment framework was adapted from the ROBINS-E tool. We conducted narrative syntheses of studies examining maternal, prenatal, and/or neonatal outcomes. We carried out meta-analyses using random effects models for five birth outcomes (i.e. birthweight, low birthweight (LBW), gestational age, pre-term birth (PTB), and small-for-gestational-age (SGA)). Studies found to be high risk of bias, or very high risk of bias were excluded from our analyses. Initial searches yielded 1099 articles. Following full text screening, our review included 62 studies. Most studies were conducted in either Europe or North America ( n = 41, 66%). All studies reported green space exposure as an independent variable while seven studies also included blue space exposure as an independent variable. The most reported green space variable was the Normalized Difference Vegetation Index (NDVI) ( n = 46, 74%). Our meta-analyses results indicated that greater greenness is protective against LBW (OR = 0.95, 95% CI: 0.92–0.98, p = 0.002), SGA (OR = 0.95, 95% CI: 0.92–0.99, p = 0.01), PTB (OR = 0.92, 95% CI: 0.88–0.97, p = 0.001), and affects birthweight ( β = 13.02 g, 95% CI: 9.99–16.05, p < 0.0001).